Etyka w bankowości – dylematy pracownika bankowego - Lipiński, Czesław (Annales. Etyka w Życiu Gospodarczym, 2008)
Credibility and reliability of counter-partners are the most important features required for the efficient functioning of financial markets. Violating these requirements is an important aspect of the operational risk, posed by the human factor – both internal (managers, employees) and external (customers, shareholders, competitors, supervisors). Therefore, having a limited impact on the behaviour of outside persons, the financial institutions formulate high standards towards their own personnel. It concerns formal qualifications and professional experience, as well as specific personality traits and appropriate behaviour in various situations. These standards are specified in numerous recent ethics codes – documents formulating the socalled ‘corporate governance best practices’ in internal and external relations to other people. The aim of this paper is to draw attention to the fact that some of these standards generate in praxis a number of dilemmas or even conflict situations, when there appears a question of to what extent the application of a given rule does not breach other rules. Theoretically, corporate governance practices should be internally consistent. However, everyday experience brings such a multitude of real situations, diverse human characters or individual reactions that there appears a need for a sensible compromise between values of equal importance which, in some cases, prove contradicting.